2012
DOI: 10.1111/j.1744-7917.2012.01581.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bacterial challenge on ferritin regulation in the yellow fever mosquito, Aedes aegypti

Abstract: Secreted ferritin is the major iron storage and transport protein in insects. Here we characterize the message and protein expression profiles of yellow fever mosquito (Aedes aegypti) ferritin heavy chain homologue (HCH) and light chain homologue (LCH) subunits in response to iron and bacterial challenge. In vivo experiments demonstrated tissue specific regulation of HCH and LCH expression over time post-blood meal (PBM). Transcriptional regulation of HCH and LCH was treatment specific, with differences in reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 86 publications
(169 reference statements)
0
12
1
Order By: Relevance
“…Animal and tissue protein extracts were loaded by the equivalent of 1 animal per lane except for eggs and first instar larvae which were loaded by the equivalent of 10 animals per lane. As noted in previous publications ( Geiser et al 2013 , Geiser et al 2015 ), purified FLAG-containing bacterial alkaline phosphatase protein (FLAG; Catalogue # P7457, Sigma, 25 ng, 50 kDa) was added to each sample as an exogenous loading control because there currently is no available cytoplasmic protein that does not change in Aedes that can serve as a good endogenous loading control, to track gel resolution and transfer of proteins to the nitrocellulose membrane. IP flow through (FT) and eluent samples (E) were loaded at 20 µl per lane, and the original experimental sample (O), 72-h PBM ovary extracts, was loaded at 30 µg per lane.…”
Section: Methodsmentioning
confidence: 99%
“…Animal and tissue protein extracts were loaded by the equivalent of 1 animal per lane except for eggs and first instar larvae which were loaded by the equivalent of 10 animals per lane. As noted in previous publications ( Geiser et al 2013 , Geiser et al 2015 ), purified FLAG-containing bacterial alkaline phosphatase protein (FLAG; Catalogue # P7457, Sigma, 25 ng, 50 kDa) was added to each sample as an exogenous loading control because there currently is no available cytoplasmic protein that does not change in Aedes that can serve as a good endogenous loading control, to track gel resolution and transfer of proteins to the nitrocellulose membrane. IP flow through (FT) and eluent samples (E) were loaded at 20 µl per lane, and the original experimental sample (O), 72-h PBM ovary extracts, was loaded at 30 µg per lane.…”
Section: Methodsmentioning
confidence: 99%
“…This immune response is observed in both Ae. aegypti and Bombyx mori (silkworm), when ferritin is upregulated during bacterial infection lending evidence that host-bacteria regulatory mechanisms involving ferritin production do exist in these organisms (Geiser et al, 2013 ; Otho et al, 2016 ). However, the signaling mechanism which determines when secretion occurs or which cell types secrete iron loaded ferritin or retain it has not been identified to date.…”
Section: Iron Packaging and Ferritin Shuttlingmentioning
confidence: 99%
“…Available evidence indicates that ferritin is critical for insect survival (Missirlis et al 2007, Tang and Zhou 2013a) and serves several roles, including the absorption, storage, and transport of iron (Georgieva et al 1999, Geiser et al 2006, Missirlis et al 2007, Zhou et al 2007, Mehta et al 2009, Tang and Zhou 2013a), in oogenesis (Walter-Nuno et al 2018), embryonic and postembryonic development (Li 2010, Gonzalez-Morales et al 2015, Rivera-Perez et al 2017), in cytotoxic protection from oxidative stress (Geiser et al 2006, 2013; Tang and Zhou 2013a), and as an immune modulator (Kremer et al 2009, Ahmed et al 2014, Gomes et al 2018). We previously reported that iron from the diet is loaded into ferritin in the Ae.…”
mentioning
confidence: 99%